Sri Lanka, a wild life interlude - Saparamadu, S. D. (Dehiwela : Tisara Prakasakayo, 2006)
Articles on wildlife consevation.
Includes bibliographical references (p. 327-330).
Keywords: Wildlife conservation -- Sri Lanka